Less Social Participation Is Associated With a Higher Risk of Depressive Symptoms Among Chinese Older Adults: A Community-Based Longitudinal Prospective Cohort Study - Min Du; Wanwei Dai; Jue Liu; Jue Liu; Jue Liu; Jing Tao (Frontiers Media S.A., 2022)
ObjectiveWe aimed to examine the association between social participation and depressive symptoms among Chinese older people aged 65 years or above to supplement limited studies in China on this topic.MethodsThis community-based longitudinal prospective cohort study used the data from the Chinese Longitudinal Healthy Longevity Survey (CLHLS, baseline in 2014 and a follow-up in 2018). Depressive symptoms were assessed using the 10-item Center for Epidemiologic Studies Depression Scale. Social participation was assessed using a composite index by considering the frequency for the two types of social activity: organized social activities and informal activities. Pearson's χ2 test was used to correlate the characteristics of participants with social participation or depressive symptoms. Log-binomial regression models were used to assess the association between social participation and the risk of depressive symptoms.ResultsThe incidence of depressive symptoms was 28.8% among 2,200 participants in 2018 after a 4-year follow-up. Participants with no social participation (32.6%), organized social activities (30.6%), or informal social activities (31.2%) were more likely to have depressive symptoms. After the adjustment of demographic factors, socioeconomic status, lifestyle habits, and health status, in comparison with older people who often engaged in social participation, organized social activities, and informal social activities, the risk of depressive symptoms was 45% [adjusted risk ratio (aRR): 1.45, 95% CI: 1.16-1.82], 42% (aRR: 1.45, 95% CI: 1.02-2.00), and 29% (aRR: 1.29, 95% CI: 1.02-1.99) higher among older people with no social participation and who never engaged in organized social activities and informal social activities, respectively.ConclusionsThis study showed that the lack of social participation, including organized social activities and informal social activities, was associated with a higher risk of depressive symptoms after 4 years among older adults in China. Our findings shed lights into the feasibility of promoting social participation to reduce the risk of depressive symptoms and promote longevity and healthy aging among older adults.